Construction and Management of a Cosmos-Based Operating System Using Visual Studio Development and VMware Virtualization Technology - Yusuf, Mohamad; Fahrezi, Zidane; Hidayah, Rafif Syari; Istanto, Yudha Andika; Saputra, Gilas Adi (Journal Collabits, 2024)
Operating systems play an important role in bridging hardware and software on various computing devices. This research focuses on building an operating system based on Cosmos, an open source project that allows the creation of operating system kernels quickly and efficiently. In the process, we leverage Visual Studio development tools to develop and maintain the kernel, while VMware virtualization technology is used to test and manage development. This research contributes to further understanding of the development of Cosmos-based operating systems with optimal use of Visual Studio development tools and VMware virtualization technology